2023
DOI: 10.3389/fsufs.2023.1197624
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microbial community structure, function, and nutrient of apple orchard soil by interplanting red clover

Abstract: Soil microbial communities are seen to be critical to the maintenance of soil health and quality. Many studies have suggested that soil microbial community composition is affected by different plant species. Based on this theory, we tried to improve the apple orchard soil microorganisms and nutrients by interplanting leguminous forage red clover (RC), meanwhile taking the natural mixed herb (NMH) naturally growing in the orchard as a control. The metagenomic analysis showed that interplanting red clover in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Changing the vegetation composition can impact soil carbon cycling by altering the quantity and quality of litter and root exudates (Ward et al, 2009 ), subsequently inducing changes in the structure and function of soil microbial communities (De Deyn et al, 2008 ). Consequently, the simultaneous presence of diverse plant species immensely important for proper ecosystem functioning (De Deyn et al, 2009 ; Jiao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the vegetation composition can impact soil carbon cycling by altering the quantity and quality of litter and root exudates (Ward et al, 2009 ), subsequently inducing changes in the structure and function of soil microbial communities (De Deyn et al, 2008 ). Consequently, the simultaneous presence of diverse plant species immensely important for proper ecosystem functioning (De Deyn et al, 2009 ; Jiao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain plants can facilitate the establishment of their neighbors by increasing soil nutrient availability (Wright et al, 2017 ), and this promoting effect can also occur indirectly through the regulatory activities of soil and microorganisms (Chen et al, 2020 ; Yu R. P. et al, 2021 ). Typically, intercropping enhances plant growth and improves the utilization efficiency of resources such as water and sunlight compared to monoculture planting (Esnarriaga et al, 2020 ; Jiao et al, 2023 ). A sugarcane and soybean intercropping experiment demonstrated that intercropping can increase the microbial diversity of rhizosphere soil, and this practice has also been widely employed to mitigate nitrogen loss and stabilize crop yield (Lian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%